2013
DOI: 10.1007/s13312-014-0380-5
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hearing screening — Experience from a tertiary care hospital in Southern India

Abstract: Neonatal hearing screening using BERAphone is a feasible service. The estimated prevalence of confirmed hearing loss was comparable to that in literature. Overcoming the large numbers of loss to follow-up proves to be a challenge in the implementation of such a program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 15 publications
2
27
1
Order By: Relevance
“…Of the total 2534 neonates screened by the two stage DPOAE hearing screening protocol and final confirmatory test with BERA at the age of three months, we could detect a total of seven neonates (2 per 1000) with hearing impairment. This was in agreement with the other studies which respectively stated that the average incidence of hearing impairment in neonates was 1.8-4.00 per 1000 [9][10][11][12][13]. However, one study from Cochin shows hearing loss in 10.3 per 1000 in high risk category [14].…”
Section: Discussionsupporting
confidence: 92%
“…Of the total 2534 neonates screened by the two stage DPOAE hearing screening protocol and final confirmatory test with BERA at the age of three months, we could detect a total of seven neonates (2 per 1000) with hearing impairment. This was in agreement with the other studies which respectively stated that the average incidence of hearing impairment in neonates was 1.8-4.00 per 1000 [9][10][11][12][13]. However, one study from Cochin shows hearing loss in 10.3 per 1000 in high risk category [14].…”
Section: Discussionsupporting
confidence: 92%
“…Reported overall TEOAE referral rates for subjects from NHS programs in developing countries vary considerably from those for our study (37.9%) with referral rates of 33.2% reported for Nigeria, 30% in Brazil, and 10.5% in Turkey [7,19,37]. The overall AABR screen referral rate per subject in this study (16.7%) was 15 higher than AABR MB 11 screening programs reported from other countries such as India (9.1%), Germany (3.8%) and Turkey (2%) [35,37,43]. A number of factors contribute to the higher refer rate in our study apart from the fact that this study was not an evaluation of an existing NHS program.…”
Section: Discussioncontrasting
confidence: 58%
“…Most importantly however the higher average refer rate for both TEOAE and AABR is largely due to the large number of ears screened within 24 hours post birth. Other studies typically screened primarily before hospital discharge but at least 48 hours post birth [7,35,37,43].…”
Section: Discussionmentioning
confidence: 99%
“…The possible effect this can have on underestimating hearing loss prevalence has been lamented in several reports. A single hospital study in India reported only 58 of 164 (35.4%) infants attended for confirmatory screening (Augustine et al, 2013). Similarly, in a targeted surveillance program in England, of 69,050 infants with risk factors who were eligible for follow-up screening, appointments were accepted for barely half (55.3%) of the qualifying infants (Wood, 2013).…”
Section: Discussionmentioning
confidence: 99%